Hole pre-sealing treatment liquid and hole pre-sealing treatment method
By using a pre-sealing treatment solution of polyol compounds and ethylene oxide condensate compounds, the problems of unsatisfactory dye fixation effect and organic residue in the aluminum alloy anodized film are solved, and good dye fixation and cleaning effects are achieved, avoiding the formation of color spots.
Patent Information
- Application Number
- CN202411866046.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
AI Technical Summary
The existing nickel-free sealing method of aluminum alloy anodized film, especially organic matter sealing method, has the problem that dye fixation effect is not ideal, organic matter is prone to remain on the surface of the aluminum oxide film, and easily produces stains.
A pre-sealing treatment solution is provided, including polyol compounds and ethylene oxide condensate compounds, wherein the polyol compounds have multiple hydroxyl groups, and the ethylene oxide condensate compounds have multiple ether bonds, which can adsorb on the outer surface of the pores of the nano-film, orifice portion and even the inner wall of the pore of the aluminum anodized film, blocking the escape of dye, and have excellent dissolution ability in the aqueous solution and are easy to clean.
It achieves excellent dye fixation effect, avoids the formation of color spots, and is easy to clean, suitable for widespread use.
Smart Images

Figure BDA0005194476290000121 
Figure BDA0005194476290000171 
Figure BDA0005194476290000181
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of pre-sealing hole treatment liquid, and in particular, relates to a pre-sealing hole treatment liquid and a pre-sealing hole treatment method. Background Art
[0002] In order to improve the anti-pollution, corrosion resistance and color stability of aluminum alloy anodized film, it is usually sealed. Existing common sealing methods include boiling water sealing, steam sealing, room temperature sealing and nickel salt (nickel acetate) sealing. Nickel salt sealing is widely used in the field of 3C product shell manufacturing due to its excellent dye sealing performance, corrosion resistance and easy control of aluminum anodized film. However, in recent years, problems such as nickel allergy, nickel salt micropowder toxicity and nickel-containing wastewater discharge have received increasing attention. Therefore, it is urgently desired to develop a nickel-free sealing method with the same sealing performance as nickel salt sealing.
[0003] Among the various nickel-free inorganic salt sealing methods currently under development, the following problems still exist: the silicate sealing method easily makes the aluminum oxide film grayish, and the weight loss data of the phosphochromic acid test is not good. The cobalt salt (cobalt acetate) sealing method has good dye sealing, but the weight loss data of the phosphochromic acid test is average, and cobalt ions are also more harmful heavy metal ions. The zinc salt sealing method disclosed in US Patent US11214886 has good dye sealing, but the weight loss data of the phosphochromic acid test is not good, higher than 20mg / dm 2 The alkali metal salt and alkaline earth metal salt sealing method disclosed in Chinese patent application CN201780020265.X can obtain the same weight loss data of phosphochromic acid test as nickel salt (<10mg / dm 2 ), but its solution cannot quickly fix the dye when using acetate, resulting in serious dye escape, so it is only suitable for sealed aluminum alloy natural color products, not for sealed dyed products. When using nitrates, the dye fixation performance is improved, but it brings the problem of ammonia nitrogen discharge in wastewater. At the same time, nitrates have the risk of oxidative damage to the molecular structure of the dye (especially the chromophore), which is not conducive to the color control of the product. In addition, among the rare earth salt sealing methods (cerium salts, yttrium salts and other rare earth salts), cerium salts have better dye fixation, but the weight loss data of the phosphochromic acid test when cerium salts and other rare earth salts are sealed are all below 30mg / dm 2 above.
[0004] In the case where the above nickel-free sealing method cannot take into account the performance of dye fixation, oxide film corrosion resistance and other properties, organic sealing is a newer exploration direction. Chinese patent CN201980068025.6 discloses an organic sealing method using thickening polysaccharides obtained by plant extraction or microbial fermentation as the main component. The applicant studied the scheme and found that many kinds of thickening polysaccharides (such as gum arabic, guar gum, tragacanth gum, carboxymethyl cellulose, chitosan, etc.) provided by the scheme have limited solubility or dispersion in water, and are easy to adhere to the surface of the aluminum oxide film. Residues are difficult to wash, causing product appearance spots. The viscosity of some thickening polysaccharide solutions is relatively high, which affects the rapid progress of the aluminum oxide hydration reaction in the membrane pores, resulting in a large amount of dye escaping from the membrane pores, and the dye fixation effect and sealing quality are significantly deteriorated. Therefore, there is an urgent need to provide a new pre-sealing treatment liquid to solve the problems of the existing nickel-free sealing method of aluminum alloy anodized film, especially the organic sealing method, which has unsatisfactory dye fixing effect, organic matter easily remaining on the surface of the aluminum oxide film, and easily causing color spots. Summary of the invention
[0005] The purpose of the present application is to provide a pre-sealing treatment liquid and a pre-sealing treatment method, aiming to solve the problems of existing nickel-free sealing methods for aluminum alloy anodized films, especially organic sealing methods, which have unsatisfactory dye fixation effects, and organic matter is easily left on the surface of the aluminum oxide film, which is prone to produce color spots.
[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0007] In a first aspect, the present application provides a pre-sealing treatment liquid, the pre-sealing treatment liquid comprising at least one of a polyol compound and an ethylene oxide condensate compound; wherein the polyol compound has at least 3 hydroxyl groups and a total carbon number of 4 to 10; the ethylene oxide condensate compound has -(OCH2CH2) n -chain segment, n is 4 to 10, and the total number of carbon atoms does not exceed 20.
[0008] In some embodiments, the polyol compound and the ethylene oxide condensate compound do not contain at least one of a benzene ring and a naphthalene ring.
[0009] In some embodiments, the polyol compound and the ethylene oxide condensate compound are each selected from any one of a linear compound, a branched compound, and a cyclic compound.
[0010] In some embodiments, the functional group of the polyol compound further includes at least one of an ether bond, an amino group, a thiol group, a carboxyl group, an aldehyde group, and a carbonyl group.
[0011] In some embodiments, the functional group of the ethylene oxide condensate compound further includes at least one of a hydroxyl group, an amino group, a thiol group, a carboxyl group, an aldehyde group, and a carbonyl group.
[0012] In some embodiments, the polyol compound includes at least one of 1,2,3-butanetriol, 1,2,4-butanetriol, erythritol, 1,2,5-pentanetriol, 1,3,5-pentanetriol, pentaerythritol, 1,2,4,5-pentanetriol, xylitol, DL-arabitol, sorbitol, D-mannitol, cyclohexanepentol, cyclohexanehexaol, heptaneheptaol, octanol, nonaneoctanol, nonanenonaol, decanol, glucose, glucosamine, N-methyl-D-glucosamine, D-galactose, β-D-galactopyranosamine, methyl-β-D-galactopyranoside, and L-fucose.
[0013] In some embodiments, the ethylene oxide condensate compound includes at least one of tetraethylene glycol, pentaethylene glycol, hexaethylene glycol, heptaethylene glycol, octaethylene glycol, nonaethylene glycol, decaethylene glycol, heptaethylene glycol monomethyl ether, octaethylene glycol monomethyl ether, polyethylene glycol 200, polyethylene glycol 300, and polyethylene glycol 400.
[0014] In some embodiments, in the pre-sealing treatment solution, the mass concentration of the polyol compound and / or the ethylene oxide condensate compound is 0.1 g / L to 20 g / L.
[0015] In some embodiments, the pre-sealing treatment solution also includes a metal salt, wherein the mass concentration of the metal salt does not exceed 2 g / L; and the metal ions are selected from at least one of lithium ions, sodium ions, potassium ions, magnesium ions, calcium ions and barium ions, and the metal salt is selected from at least one of metal acetates, metal tartrates and metal organic sulfonates.
[0016] In some embodiments, the pH of the pre-sealing solution is 3.0-6.0.
[0017] In a second aspect, the present application provides a method for pre-sealing holes of an aluminum alloy anodized film, comprising the following steps:
[0018] Providing an aluminum alloy anodized film to be treated and the above-mentioned pre-sealing treatment solution;
[0019] The aluminum alloy anodized film to be treated is subjected to a pre-pore sealing treatment by using a pre-pore sealing treatment liquid, and then washed with water to obtain the aluminum alloy anodized film after the pre-pore sealing treatment.
[0020] In some embodiments, the pre-sealing treatment is performed at a temperature of 90 to 100° C. for a time of 2 to 20 minutes.
[0021] The pre-sealing treatment liquid provided in the first aspect of the present application includes at least one of a polyol compound and an ethylene oxide condensate compound; the provided polyol compound has multiple hydroxyl groups, and the ethylene oxide condensate compound has multiple ether bonds. The hydroxyl groups or ether bonds contained therein have good wettability to the aluminum anodized film and can be adsorbed on the outer surface of the nano-membrane pores, the pore mouth and even the inner wall of the pores of the anode film. The steric hindrance of these molecules can block the escape of the dye in the pores, and has a good pre-blocking and fixing effect on the dye in the membrane pores. At the same time, the polyol compound and / or the ethylene oxide condensate compound has excellent solubility in aqueous solution, is easy to clean, does not form a large amount of adhesion residue, and avoids the formation of color spots; therefore, the provided pre-sealing treatment liquid has an excellent dye fixing effect and is easy to clean, which is conducive to wide use.
[0022] The second aspect of the present application provides a pre-sealing treatment method for an anodized film. In the pre-treatment method, a pre-sealing treatment liquid is used for pre-sealing treatment. The pre-sealing treatment can effectively fix the dye and reduce the dye from seeping out of the pores of the aluminum oxide film. After washing with water, no much sticky organic matter will remain, which facilitates the subsequent sealing treatment. The sealed aluminum oxide film has excellent corrosion resistance and pollution resistance, and at the same time has a good color appearance, without color spots or other poor color uniformity problems. DETAILED DESCRIPTION
[0023] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0024] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0025] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0026] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0027] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0028] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass in the embodiment description of the present application can be μg, mg, g, kg and other mass units known in the chemical industry.
[0029] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0030] In a first aspect, an embodiment of the present application provides a pre-sealing treatment liquid, the pre-sealing treatment liquid comprises at least one of a polyol compound and an ethylene oxide condensate compound; wherein the polyol compound has at least 3 hydroxyl groups and a total carbon number of 4 to 10; the ethylene oxide condensate compound has -(OCH2CH2) n -chain segment, n is 4 to 10, and the total number of carbon atoms does not exceed 20.
[0031] The pre-sealing treatment liquid provided in the first aspect of the embodiment of the present application includes at least one of a polyol compound and an ethylene oxide condensate compound; the provided polyol compound has multiple hydroxyl groups, and the ethylene oxide condensate compound has multiple ether bonds. The hydroxyl groups or ether bonds contained in the polyol compound have good wettability to the aluminum anodized film and can be adsorbed on the outer surface of the nano-membrane pores, the pore mouth and even the inner wall of the pores of the anode film. The steric hindrance of these molecules can block the escape of the dye in the pores, and has a good pre-blocking and fixing effect on the dye in the membrane pores. At the same time, the polyol compound and / or the ethylene oxide condensate compound has excellent solubility in aqueous solution, is easy to clean, does not form a large amount of adhesion residue, and avoids the formation of color spots; therefore, the provided pre-sealing treatment liquid has an excellent dye fixing effect and is easy to clean, which is conducive to wide use.
[0032] The pre-sealing treatment liquid includes at least one of a polyol compound and an ethylene oxide condensate compound. On the one hand, the polyol compound and / or the ethylene oxide condensate compound has good wettability to the surface of the aluminum anodized film, and can form weak adsorption on the surface of the aluminum oxide film, the membrane pore mouth and even the inner wall of the membrane pore. When the hydrated aluminum oxide formed by the hydration reaction of aluminum oxide in the membrane pore at high temperature is not enough to block the membrane pore mouth, these organic substances have a certain blocking effect on the escape of the dye in the membrane pore. On the other hand, the polyol compound and / or the ethylene oxide condensate compound has good water solubility and only forms weak adsorption on the surface of the oxide film, which is convenient for washing and removal after the sealing treatment, and will not form a large amount of residue, thereby avoiding the generation of undesirable problems such as color spots or rainbow colors.
[0033] Among them, the number of hydroxyl groups of the polyol compound is not less than 3, and the total number of carbon atoms is 4 to 10. The number of hydroxyl groups of the polyol compound is limited to not less than 3: first, it can have good wetting and sufficient adsorption on the surface of the workpiece, to a certain extent, block the escape of the dye in the nanopores of the aluminum oxide film, which is conducive to improving the dye fixation effect; second, it can have good water solubility, and it is not easy to form insoluble or viscous substances adhering to the surface of the workpiece, causing problems such as difficulty in cleaning and more residues; the total number of carbon atoms is controlled to be 4 to 10. If the number of carbon atoms exceeds 10, the viscosity of the polyol compound increases, and it is easy to adhere to the surface of the workpiece to cause more residues, and there will be residues and color spots; if the total number of carbon atoms is less than 4, although it is easy to enter the nanopores of the aluminum oxide film and adsorb on the inner wall, due to the small size of the molecule, the steric hindrance is small, which is not conducive to blocking the escape of the dye in the nanopores, and the dye fixation effect becomes worse.
[0034] Ethylene oxide condensation compounds have -(OCH2CH2) n-segment, n is 4 to 10, and the total number of carbon atoms does not exceed 20. The number of segments is limited to 4 to 10. First, it can have good wetting and sufficient adsorption on the surface of the workpiece, which can block the escape of the dye in the nanopores of the aluminum oxide film to a certain extent, which is beneficial to improve the dye fixation effect; secondly, it can have good water solubility, and it is not easy to form insoluble or viscous substances adhering to the surface of the workpiece, causing problems such as difficulty in cleaning and more residues. The total number of carbon atoms of ethylene oxide condensation compounds is limited to no more than 20. If the number of carbon atoms exceeds 20, it will also cause the viscosity of the compound to increase, resulting in residue and color spot problems; if the number of carbon atoms is too small, the molecule is small and the steric hindrance is small, which is not conducive to blocking the escape of the dye in the nanopores, and the dye fixation effect becomes worse.
[0035] In some embodiments, the polyol compounds and the ethylene oxide condensate compounds do not contain at least one of a benzene ring and a naphthalene ring. The benzene ring structure and the naphthalene ring structure have good affinity for organic dyes, and can "drag" the organic dye molecules out of the membrane pores by molecular thermal motion in the high-temperature sealing liquid, thereby increasing the escape of the dye; therefore, the provided polyol compounds and the ethylene oxide condensate compounds do not contain a benzene ring or a naphthalene ring.
[0036] In some embodiments, the polyol compound and the ethylene oxide condensate compound are each selected from any one of a linear compound, a branched compound, and a cyclic compound, without particular limitation.
[0037] In some embodiments, the functional groups of the polyol compounds also include at least one of ether bonds, amino groups, sulfhydryl groups, carboxyl groups, aldehyde groups and carbonyl groups. In some embodiments, the functional groups of ethylene oxide condensate compounds also include at least one of hydroxyl groups, amino groups, sulfhydryl groups, carboxyl groups, aldehyde groups and carbonyl groups. In order to avoid these other groups from forming strong adsorption on the surface and being difficult to clean, the total number of the above-mentioned other functional groups except hydroxyl groups and ether bonds in the provided polyol compounds / ethylene oxide condensate compounds molecules does not exceed 2.
[0038] In some embodiments, the polyol compound includes at least one of 1,2,3-butanetriol, 1,2,4-butanetriol, erythritol, 1,2,5-pentanetriol, 1,3,5-pentanetriol, pentaerythritol, 1,2,4,5-pentanetriol, xylitol, DL-arabitol, sorbitol, D-mannitol, cyclohexanepentol, cyclohexanehexaol, heptaneheptaol, octanol, nonaneoctanol, nonanenonaol, decanol, glucose, glucosamine, N-methyl-D-glucosamine, D-galactose, β-D-galactopyranosamine, methyl-β-D-galactopyranoside, and L-fucose.
[0039] In some embodiments, the ethylene oxide condensate compound includes at least one of tetraethylene glycol, pentaethylene glycol, hexaethylene glycol, heptaethylene glycol, octaethylene glycol, nonaethylene glycol, decaethylene glycol, heptaethylene glycol monomethyl ether, octaethylene glycol monomethyl ether, polyethylene glycol 200, polyethylene glycol 300, and polyethylene glycol 400.
[0040] In some embodiments, the mass concentration of the polyol compound and / or the ethylene oxide condensate compound is 0.1g / L to 20g / L. When the mass concentration of the polyol compound and / or the ethylene oxide condensate compound is less than 0.1g / L, the effect of inhibiting the escape of dyes in the membrane pores is significantly deteriorated. On the contrary, when the mass concentration of the polyol compound and / or the ethylene oxide condensate compound is greater than 20g / L, the further improvement of the effect of inhibiting the escape of dyes in the membrane pores is not obvious, but may cause difficulties in cleaning, and the cost will also increase. From the perspective of balancing the effect of inhibiting the escape of dyes and cost control, the mass concentration of the polyol compound and / or the ethylene oxide condensate compound is further preferably 0.5g / L to 10g / L.
[0041] In some embodiments, the pH of the pre-sealing treatment liquid is 3.0 to 6.0. Within this pH range, the pre-sealing treatment liquid has a good dye fixing effect, and the aluminum anodized film after sealing has excellent corrosion resistance and pollution resistance. Controlling the pH of the pre-sealing treatment liquid to be weakly acidic can increase the speed of fixing the dye. Weak acidity can slightly corrode the amorphous aluminum oxide pore wall, release a small amount of aluminum ions, and thus can reprecipitate hydrated aluminum oxide to form a boehm body, thereby accelerating the speed of blocking and closing the pores, especially the pore openings, and reducing the leakage of dyes in the pores. If the pH is too small, the solution is acidic, the corrosion of the membrane pores is too large, the pore size becomes significantly larger, and the sealing becomes difficult. In severe cases, the entire anodized film is corroded and collapsed. If the pH is too large, the solution is neutral or weakly alkaline, the color fixation speed slows down, and the color fixation time needs to be extended, thereby increasing the number of dye leaks, and strong alkalinity can cause serious corrosion to the aluminum oxide film. In some preferred embodiments, the pH of the pre-sealing treatment liquid is 3.5 to 5.0.
[0042] In some embodiments, the pre-sealing treatment solution further includes a metal salt, wherein the mass concentration of the metal salt does not exceed 2 g / L; when the mass concentration of the metal salt exceeds 2 g / L, the effect of inhibiting dye escape will be significantly deteriorated.
[0043] Among them, in the metal salt, the metal ion is selected from at least one of lithium ion, sodium ion, potassium ion, magnesium ion, calcium ion and barium ion. The provided metal salt does not involve harmful heavy metal ions such as nickel, cobalt and chromium, and is safe and environmentally friendly. A small amount of metal salt can enter the inside of the anode film pores for pre-sealing, which will not cause obvious escape of dye, but can improve the corrosion resistance of the aluminum anodized film.
[0044] The metal salt is selected from at least one of metal acetate, metal tartrate, and metal organic sulfonate. In some specific embodiments, the sodium salt can be added in the form of sodium tartrate as a complexing agent, or can be added in the form of naphthalenesulfonic acid formaldehyde condensation polymer sodium salt as a gray suppressant.
[0045] In some embodiments, the pre-sealing treatment liquid of the present application embodiment may further contain various buffers, pH adjusting agents, complexing agents, ash suppressants, mildew inhibitors and other additives known in the art, without particular limitation. As buffers known in the art, examples such as boric acid and borates, amino acids and amino acid salts, carboxylic acids and carboxylates and organic amines may be cited. As pH adjusting agents known in the art, examples of aqueous solutions such as acetic acid, nitric acid, aminosulfonic acid, methanesulfonic acid, ammonia, sodium hydroxide, potassium hydroxide and triethanolamine may be cited, and acetic acid aqueous solution and sodium hydroxide aqueous solution are preferred from the perspective of sealing effect. As complexing agents known in the art, examples such as tartaric acid and tartrates, citric acid and citrates, amino acids and amino acid salts, ethylenediaminetetraacetic acid and ethylenediaminetetraacetic acid sodium salt may be cited. As the well-known anti-dust agent in the art, generally various surfactants can prevent the formation of gray or other colored powder frosting on the surface of aluminum anodized film, examples of which include fatty alcohol polyoxyethylene ether, nonylphenol polyoxyethylene ether, polyoxyethylene alkyl ether sulfate, polyoxyethylene alkylphenyl ether sulfate, naphthalene sulfonic acid formaldehyde condensation product sodium salt, alkyl diphenyl ether disulfonate, etc. As the well-known anti-mold agent in the art, examples of which include benzoic acid, benzoate, oxazolidine-2,5-dione and other oxazolidines, etc.
[0046] The pre-sealing treatment solution provided in the embodiment of the present application can be used directly as a stock solution, or it can be prepared into a concentrated solution of different multiples such as 5 times, 10 times, 20 times, 50 times, etc., and then be used after being appropriately diluted with deionized water or pure water.
[0047] In a second aspect, the present application provides a method for pre-sealing holes of an aluminum alloy anodized film, comprising the following steps:
[0048] S01. Providing an aluminum alloy anodized film to be treated and the above-mentioned pre-sealing treatment solution;
[0049] S02. The aluminum alloy anodized film to be treated is subjected to a pore sealing pretreatment using a pre-pore sealing treatment liquid, and then washed with water to obtain an anodized film after the pre-pore sealing treatment.
[0050] In a pre-sealing treatment method for an aluminum alloy anodized film provided in the second aspect of an embodiment of the present application, a pre-sealing treatment liquid is used for sealing pretreatment, which can effectively fix the dye, reduce the dye from seeping out of the pores of the aluminum oxide film, stabilize the color value, and will not leave much sticky organic matter after washing, so that the sealed aluminum alloy oxide film has a good color appearance, without color spots or other poor color uniformity problems.
[0051] In step S01, an aluminum alloy anodized film to be treated and the above-mentioned pre-sealing treatment liquid are provided; the pre-sealing treatment liquid provided is the pre-sealing treatment liquid discussed above, and will not be described again here to save space.
[0052] In step S02, the anodic oxide film to be treated is pre-sealed with a pre-sealing treatment liquid, and then washed with water to obtain the anodic oxide film after the pre-sealing treatment. The pre-sealing treatment can effectively fix the dye, and when the subsequent sealing treatment is performed, more dye will not seep out of the pores of the aluminum oxide film.
[0053] In some embodiments, the temperature of the pre-sealing treatment is 90-100°C and the time is 2-20 minutes. The temperature of the pre-sealing treatment is 90-100°C. When the treatment is performed at the pre-sealing treatment temperature, the dye has a rapid dye fixing effect; the temperature of the pre-sealing treatment is preferably 95-99°C. The time of the pre-sealing treatment is 2-20 minutes. When the pre-sealing treatment is performed at this time, the pre-sealing treatment liquid has a sufficient dye fixing effect. The time of the pre-sealing treatment is preferably 5-10 minutes.
[0054] Furthermore, the water washing is not limited to the number of water washing times, and 1 to several water washing tanks may be used, preferably 2 to 4 water washing tanks.
[0055] After washing with water, an anodic oxide film after pre-sealing treatment is obtained.
[0056] Furthermore, the anodized film obtained after the pre-sealing treatment needs to be subsequently sealed with a conventional metal salt treatment solution, and then washed and baked to complete the complete sealing of the pores of the aluminum oxide film.
[0057] In some embodiments, the metal salt treatment solution includes but is not limited to at least one of metal salts of lithium, sodium, potassium, magnesium, calcium and barium. The metal salt includes but is not limited to at least one of metal acetate, metal tartrate and metal organic sulfonate.
[0058] In some embodiments, the mass concentration of the metal salt in the metal treatment solution is not particularly limited. In some possible embodiments, the mass concentration of the metal salt in the metal salt treatment solution is 0.1 g / L to 100 g / L, specifically 0.1 g / L, 1 g / L, 2 g / L, 5 g / L, 10 g / L, 50 g / L, 100 g / L, etc.
[0059] In certain embodiments, the metal salt treatment solution of the present application embodiment may further contain various buffers, pH adjusting agents, complexing agents, ash suppressants, mildew inhibitors and other additives known in the art, without particular limitation. As buffers known in the art, examples such as boric acid and borates, amino acids and amino acid salts, carboxylic acids and carboxylates and organic amines may be cited. As pH adjusting agents known in the art, examples of aqueous solutions such as acetic acid, nitric acid, aminosulfonic acid, methylsulfonic acid, ammonia, sodium hydroxide, potassium hydroxide and triethanolamine may be cited, and acetic acid aqueous solution and sodium hydroxide aqueous solution may be preferred from the perspective of sealing effect. As complexing agents known in the art, examples such as tartaric acid and tartrates, citric acid and citrates, amino acids and amino acid salts, ethylenediaminetetraacetic acid and ethylenediaminetetraacetic acid sodium salt may be cited. As the well-known anti-dust agent in the art, generally various surfactants can prevent the formation of gray or other colored powder frosting on the surface of aluminum anodized film, examples of which include fatty alcohol polyoxyethylene ether, nonylphenol polyoxyethylene ether, polyoxyethylene alkyl ether sulfate, polyoxyethylene alkylphenyl ether sulfate, naphthalene sulfonic acid formaldehyde condensation product sodium salt, alkyl diphenyl ether disulfonate, etc. As the well-known anti-mold agent in the art, examples of which include benzoic acid, benzoate, oxazolidine-2,5-dione and other oxazolidines, etc.
[0060] In some embodiments, the pH of the metal salt treatment solution is preferably 5.0 to 9.0. Within this pH range, the sealed aluminum anodized film has excellent corrosion resistance and pollution resistance.
[0061] In some embodiments, the temperature of the subsequent sealing treatment is 90-100°C and the time is 20-90 minutes. The temperature of the subsequent sealing treatment is controlled to be 90-100°C so that the metal salt treatment solution has an excellent sealing effect; wherein, the temperature of the subsequent sealing treatment is preferably 95-99°C; the time of the subsequent sealing treatment is preferably 30-60 minutes. In actual sealing operations, the appropriate subsequent sealing time is usually selected according to the film thickness of the aluminum anodized film. Generally, the greater the thickness of the aluminum anodized film, the longer the corresponding subsequent sealing time.
[0062] The washing step is then performed with water, and the number of washing times is not limited. The washing step may include 1 to several washing tanks, preferably 2 to 4 washing tanks.
[0063] In some embodiments, the baking process is performed at a temperature of 50 to 80° C. and a time of 20 to 50 minutes.
[0064] The following describes the invention in conjunction with specific embodiments.
[0065] Several 6063 aluminum alloy test pieces with a size of 50 mm×50 mm×1.5 mm were taken and processed according to the steps and conditions shown in Table 1 below to prepare test pieces with a film thickness of 14 to 15 μm for the sealing treatment test used in the following embodiments and comparative examples.
[0066] Table 1
[0067]
[0068]
[0069] The test pieces after the sealing treatment prepared in the following Examples and Comparative Examples were evaluated using the following test methods.
[0070] [Appearance evaluation]
[0071] After the sealing treatment, observe the surface of the test piece for powdery frost, gray fog, color spots or organic residues and record them. If there are no such appearance defects and the color is uniform, it can be considered that the appearance of the test piece has no problem in actual use.
[0072] [Dye fixing effect]
[0073] Use a spectrophotometer to measure the L, a, and b color values of the test piece after dyeing (blow dry with cold air and let stand for 30 minutes before measuring the color. After the color measurement is completed, soak it in pure water for about 10 minutes before pre-sealing and subsequent sealing) and sealing. Use the L value after dyeing (L1) as a benchmark, and compare it with the L value after sealing (L2). Calculate ΔL=L2-L1 to represent the change in color depth of the test piece before and after sealing. Roughly evaluate the degree of dye escape from the test piece during the sealing process, which is used to evaluate the dye fixing effect of the pre-sealing treatment solution. The evaluation criteria are as follows:
[0074] ◎: ΔL<1.0
[0075] ○: 1.0≤ΔL<3.0
[0076] △: 3.0≤ΔL<5.0
[0077] ×: ΔL ≥ 5.0
[0078] If the evaluation is ○ or ◎, it can be considered that the dye fixing effect of the pre-sealing treatment liquid has no problem in practical use.
[0079] [Sealing quality]
[0080] Refer to the "Phosphochromic Acid Method without Nitric Acid Pre-immersion" in GB / T 8753.1-2017 "Aluminum and Aluminum Alloy Anodizing (Evaluation Method for Oxide Film Sealing Quality) Part 1: Acid Etching Weight Loss Method", immerse each test piece after sealing treatment in a phosphoric acid-chromic acid aqueous solution at (38±1)℃ for 15 minutes, and weigh and calculate the weight loss per unit area of the test piece after cleaning and drying. The smaller the value, the better the sealing quality and the better the corrosion resistance of the aluminum anodized film after sealing. If the weight loss is less than 15mg / dm 2 , it can be considered that the sealing quality of the pre-sealing treatment liquid has no problem in actual use.
[0081] [Pollution resistance]
[0082] After the sealing treatment, place each test piece at room temperature for 1 day, draw a line segment mark of about 1 cm long and 1 mm wide on the surface of the test piece with an oily black marker, and leave it for 60 seconds. Then wipe it with a dust-free paper soaked in water or isopropyl alcohol, and rate it according to the following standards:
[0083] ◎: Can completely remove the mark
[0084] ○: The mark can be removed, but a slight trace will remain
[0085] △: Only part of the mark can be removed
[0086] ×: Black mark cannot be removed
[0087] If the test evaluation of removing the mark with water is ○ or ◎, it can be considered that the stain resistance performance of the test piece has no problem in practical use.
[0088] It should be pointed out that the same test piece cannot be used to evaluate the sealing quality and the pollution resistance successively. Only two test pieces prepared under the same conditions can be used to evaluate the sealing quality and the pollution resistance respectively, otherwise the results will interfere with each other.
[0089] The chemical reagents used in the following examples and comparative examples were all analytically pure, and the water used was all deionized water.
[0090] Example 1
[0091] Sealing treatment method
[0092] (1) Perform pre-sealing treatment first;
[0093] Providing a pre-sealing treatment solution, wherein the pre-sealing treatment solution includes 1 g / L of xylitol and the pH is adjusted to 4.2 with acetic acid;
[0094] The test piece to be treated was pre-sealed in a pre-sealing treatment solution heated to 97° C. for 10 minutes, and then subjected to two ordinary water washing treatments, each of which lasted for 60 seconds.
[0095] (2) Follow-up sealing treatment:
[0096] A metal salt treatment solution is provided, wherein the metal salt treatment solution includes 5g / L magnesium acetate tetrahydrate, 1g / L boric acid, 0.5g / L naphthalenesulfonic acid formaldehyde condensation product sodium salt and 0.1g / L lauryl alcohol polyoxyethylene ether, and the pH is adjusted to 5.5 with acetic acid.
[0097] After the pre-sealing treatment, the test piece was sealed in a metal salt treatment solution heated to 97°C for 50 minutes, and then subjected to 2 ordinary water washing treatments and 1 ultrasonic water washing treatment, with the washing time being 60 seconds each.
[0098] Dry at 60℃ for 30min, take out and place in a dryer to stand naturally for more than 24h.
[0099] (3) Then the appearance, dye fixation effect, sealing quality and stain resistance were evaluated. The treatment conditions and effect evaluation are recorded in the following Tables 2 and 3 respectively.
[0100] Example 2
[0101] Compared with Example 1, the pre-sealing treatment liquid is modified to "1 g / L pentaerythritol, 0.2 g / L naphthalenesulfonic acid formaldehyde condensation product sodium salt, and the pH is adjusted to 4.2 with acetic acid"; the other contents are the same as Example 1.
[0102] Example 3
[0103] Compared with Example 2, the "1 g / L pentaerythritol" in the pre-sealing treatment solution is changed to "5 g / L D-mannitol"; the other contents are the same as in Example 2.
[0104] Example 4
[0105] Compared with Example 2, the "1 g / L pentaerythritol" in the pre-sealing treatment liquid is changed to "1 g / L cyclohexanehexol"; the other contents are the same as Example 2.
[0106] Example 5
[0107] Compared with Example 2, the "1 g / L pentaerythritol, pH adjusted to 4.2" in the pre-sealing treatment liquid is modified to "1 g / L pentaethylene glycol, pH adjusted to 4.0"; the other contents are the same as Example 2.
[0108] Example 6
[0109] Compared with Example 2, the "1 g / L pentaerythritol, pH adjusted to 4.2" in the pre-sealing treatment solution is modified to "1 g / L polyethylene glycol 200, pH adjusted to 4.0"; the other contents are the same as Example 2.
[0110] Example 7
[0111] Compared with Example 6, the "1 g / L polyethylene glycol 200" in the pre-sealing treatment solution is changed to "5 g / L polyethylene glycol 200"; the other contents are the same as Example 6.
[0112] Example 8
[0113] Compared with Example 6, "0.5 g / L of magnesium acetate tetrahydrate" is added to the pre-sealing treatment liquid; the other contents are the same as those in Example 6.
[0114] Example 9
[0115] Relative to Example 8, "0.5 g / L of magnesium acetate tetrahydrate" in the pre-sealing treatment liquid is changed to "0.5 g / L of calcium acetate monohydrate", "magnesium acetate tetrahydrate" in the metal salt treatment liquid is changed to "2 g / L of calcium acetate monohydrate", and "boric acid" is changed to "1 g / L of glutamic acid", and the other contents are the same as Example 8.
[0116] Example 10
[0117] Relative to Example 9, "1 g / L polyethylene glycol 200" in the pre-sealing treatment liquid is changed to "1 g / L pentaethylene glycol", "0.5 g / L calcium acetate monohydrate" is changed to "0.5 / L magnesium acetate tetrahydrate", and "2 g / L calcium acetate monohydrate" in the metal salt treatment liquid is changed to "2 g / L magnesium acetate tetrahydrate", and the other contents are the same as Example 9.
[0118] Embodiment 11
[0119] Compared with Example 10, the concentration of magnesium acetate tetrahydrate in the pre-sealing treatment solution was adjusted from 0.5 g / L to 2 g / L, and the other contents were the same as those in Example 10.
[0120] Example 12
[0121] Compared with Example 10, the pre-sealing treatment time is shortened from 10 min to 5 min, and other treatment conditions are the same as those of Example 10.
[0122] Comparative Example 1
[0123] Compared with Example 1, 5 g / L sodium carboxymethyl cellulose was used in the pre-sealing treatment solution instead of xylitol, and other treatment conditions were the same as those in Example 1.
[0124] During the sealing pretreatment step, dye leakage was serious, and the L value of the test piece increased by ΔL by 19.7 after the sealing treatment.
[0125] Comparative Example 2
[0126] Compared with Example 1, 1 g / L chitosan was used in the pre-sealing treatment solution instead of xylitol, and other treatment conditions were the same as those in Example 1.
[0127] Comparative Example 3
[0128] Compared with Example 1, 1 g / L guar gum was used in the pre-sealing treatment solution instead of xylitol, and other treatment conditions were the same as those in Example 1.
[0129] Comparative Example 4
[0130] Compared with Example 1, the pre-sealing treatment liquid used 1 g / L chitosan instead of xylitol, and the other treatment conditions were the same as those in Example 1.
[0131] Comparative Example 5
[0132] Compared with Example 1, the pre-sealing treatment liquid used 5 g / L of gum arabic instead of xylitol, and the other treatment conditions were the same as those in Example 1.
[0133] Comparative Example 6
[0134] Compared with Example 1, 1 g / L tetraethylene glycol monobenzyl ether was used in the pre-sealing treatment solution instead of xylitol, and other treatment conditions were the same as those of Example 1. During the pre-sealing treatment step, dye leakage was serious.
[0135] Comparative Example 7
[0136] Compared with Example 1, 1 g / L 1,5-naphthalene disulfonic acid was used in the pre-sealing treatment solution instead of xylitol, and other treatment conditions were the same as those of Example 1. During the pre-sealing treatment step, dye leakage was serious.
[0137] Comparative Example 8
[0138] A nickel salt sealing agent Top Seal DX-500 (manufactured by Okuno Pharmaceutical Co., Ltd.) was used to prepare a 10 g / L solution with a pH of 5.6, and a one-step sealing was performed at a temperature of 97° C. for 60 minutes.
[0139] Table 2
[0140]
[0141]
[0142]
[0143]
[0144] Table 3
[0145]
[0146]
[0147] According to Table 2 and Table 3, it can be found that in Examples 1 to 12, the pre-sealing treatment liquid containing the polyol compound or ethylene oxide condensate compound provided in the embodiment of the present application is used for the pre-sealing treatment step, which has a good fixing effect on the dye. At the same time, these organic substances have good water solubility, suitable molecular size, and moderate affinity for the surface of the aluminum oxide film, and will not adhere to the surface of the test piece in large quantities, causing difficult cleaning and residual problems. In addition, the use of a metal salt treatment liquid containing lithium, sodium, potassium, magnesium, calcium or barium for subsequent sealing treatment steps can obtain a sealing quality and pollution resistance close to or equivalent to that of a nickel salt sealer. In contrast, in Comparative Examples 1 to 5, a pre-sealing treatment liquid containing a thickening polysaccharide is used for the pre-sealing treatment step. Because the molecules of these thickening polysaccharides are relatively large and the water solubility is generally not high, the viscosity of the solution is relatively large. These polysaccharide substances are easily adhered to the surface of the test piece in large quantities, which is difficult to clean, forming more organic residues, and color spots, dark spots and other color unevenness problems appear in appearance. Among them, the sodium carboxymethyl cellulose in Comparative Example 1 has a large viscosity in the solution, and can form a large number of carboxyl groups under acidic conditions. It not only has no color fixation effect, but also causes the dye in the membrane pores to escape into the solution in large quantities. Comparative Examples 6 and 7 use treatment solutions containing organic compounds with smaller molecules and benzene ring structures and / or naphthalene ring structures to fix dyes, and the effect is significantly deteriorated, and serious dye escape occurs. Comparative Example 8 is a typical nickel salt sealing treatment scheme, and its effect can be used as a reference for the effects of the above embodiments and other comparative examples. According to the effects of the above embodiments and comparative examples, the pre-sealing treatment solution and pre-sealing treatment method provided by the present application are significantly progressive.
[0148] In summary, the pre-sealing treatment liquid provided in the embodiments of the present application includes at least one of a polyol compound and an ethylene oxide condensate compound; the provided polyol compound has multiple hydroxyl groups, and the ethylene oxide condensate compound has multiple ether bonds. The hydroxyl group or ether bond functional group contained has good wettability to the aluminum anodized film, and can be adsorbed on the outer surface of the nano-membrane pores of the anode film, the pore mouth and even the inner wall of the pores. The steric hindrance of these molecules can block the escape of the dye in the pores, and has a good pre-blocking and fixing effect on the dye in the membrane pores. At the same time, the polyol compound and / or the ethylene oxide condensate compound has excellent solubility in aqueous solution, is easy to clean, will not form a large amount of adhesion residue, and avoids the formation of color spots; therefore, the provided pre-sealing treatment liquid has an excellent dye fixing effect and is easy to clean, which is conducive to wide use.
[0149] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A pre-sealing treatment liquid, characterized in that: The pre-sealing treatment liquid comprises at least one of a polyol compound and an ethylene oxide condensate compound; wherein the polyol compound has at least 3 hydroxyl groups and a total carbon number of 4 to 10; and the ethylene oxide condensate compound has -(OCH2CH2) n -chain segment, n is 4 to 10, and the total number of carbon atoms does not exceed 20.
2. The pre-sealing hole treatment liquid according to claim 1, characterized in that: The polyol compound and the ethylene oxide condensate compound do not contain at least one of a benzene ring and a naphthalene ring.
3. The pre-sealing hole treatment liquid according to claim 1, characterized in that: The polyol compound and the ethylene oxide condensate compound are each selected from any one of a linear compound, a branched compound, and a cyclic compound.
4. The pre-sealing treatment liquid according to claim 1, characterized in that: The functional group of the polyol compound further includes at least one of an ether bond, an amino group, a thiol group, a carboxyl group, an aldehyde group and a carbonyl group; and / or, The functional group of the ethylene oxide condensate compound further includes at least one of a hydroxyl group, an amino group, a thiol group, a carboxyl group, an aldehyde group and a carbonyl group.
5. The pre-sealing hole treatment liquid according to claim 1, characterized in that: The polyol compound includes at least one of 1,2,3-butanetriol, 1,2,4-butanetriol, erythritol, 1,2,5-pentanetriol, 1,3,5-pentanetriol, pentaerythritol, 1,2,4,5-pentanetriol, xylitol, DL-arabitol, sorbitol, D-mannitol, cyclohexanepentol, cyclohexanehexol, heptaneheptanol, octanol, nonaneoctanol, nonanenonaol, decanol, glucose, glucosamine, N-methyl-D-glucosamine, D-galactose, β-D-galactopyranosamine, methyl-β-D-galactopyranoside, and L-fucose; and / or, The ethylene oxide condensate compound includes at least one of tetraethylene glycol, pentaethylene glycol, hexaethylene glycol, heptaethylene glycol, octaethylene glycol, nonaethylene glycol, decaethylene glycol, heptaethylene glycol monomethyl ether, octaethylene glycol monomethyl ether, polyethylene glycol 200, polyethylene glycol 300, and polyethylene glycol 400.
6. The pre-sealing hole treatment liquid according to claim 1, characterized in that: In the pre-sealing treatment liquid, the mass concentration of the polyol compound and / or the ethylene oxide condensate compound is 0.1 g / L to 20 g / L.
7. The pre-sealing treatment liquid according to any one of claims 1 to 6, characterized in that: The pre-sealing treatment solution also includes a metal salt; wherein the mass concentration of the metal salt does not exceed 2 g / L; and the metal ions are selected from at least one of lithium ions, sodium ions, potassium ions, magnesium ions, calcium ions and barium ions, and the metal salt is selected from at least one of metal acetates, metal tartrates and metal organic sulfonates.
8. The pre-sealing treatment liquid according to any one of claims 1 to 6, characterized in that: The pH of the pre-sealing treatment solution is 3.0-6.
0.
9. A method for pre-sealing holes of an aluminum alloy anodized film, characterized in that: The steps include: Providing an aluminum alloy anodized film to be treated and a pre-sealing treatment solution according to any one of claims 1 to 8; The pre-sealing treatment liquid is used to perform pre-sealing treatment on the aluminum alloy anodized film to be treated, and then the film is washed with water to obtain the aluminum alloy anodized film after the pre-sealing treatment.
10. The pre-sealing method for anodized aluminum alloy film according to claim 9, characterized in that: The pre-sealing treatment is performed at a temperature of 90 to 100° C. and for a time of 2 to 20 minutes.
Citation Information
Patent Citations
Sealing liquid for anodic oxide coating films of aluminum alloy, concentrated liquid and sealing method
CN108884586A
Pore-sealing treatment solution for anodic oxide coating film on aluminum alloy
CN112867815A
Zinc-based seal for anodized parts
US11214886B2